2022
DOI: 10.1111/jfpp.16717
|View full text |Cite
|
Sign up to set email alerts
|

Lipid characteristics, bioactive properties, and mineral content in hazelnut grown under different cultivation systems

Abstract: The demand for organic food is increasing due to the view among consumers that organic food is healthier and more nutritious. However, very limited data are available on the nutritional content of organic hazelnuts. The aim of this study was to compare the chemical and nutraceutical properties of Prime Quality hazelnuts grown with organic and conventional farming systems under the same climatic conditions. For this purpose, approximate, fatty acid, sterol and tocopherol composition, total phenolic, total flavo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 49 publications
(93 reference statements)
2
8
1
1
Order By: Relevance
“…The PCA showed a positive correlation between a higher content of oleic acid (C18:1) and a higher antioxidant activity, which was also observed in hazelnuts. 77 Nevertheless, it was also observed that organic hazelnuts showed higher total sterol and sitosterol contents than conventional ones, whereas, in the present study, no significant differences were observed between the organic and conventional samples. Additionally, the PCA correlated a higher content of sterols with a lower antioxidant activity, which was already reported in other studies.…”
Section: Fruit Membranescontrasting
confidence: 76%
See 1 more Smart Citation
“…The PCA showed a positive correlation between a higher content of oleic acid (C18:1) and a higher antioxidant activity, which was also observed in hazelnuts. 77 Nevertheless, it was also observed that organic hazelnuts showed higher total sterol and sitosterol contents than conventional ones, whereas, in the present study, no significant differences were observed between the organic and conventional samples. Additionally, the PCA correlated a higher content of sterols with a lower antioxidant activity, which was already reported in other studies.…”
Section: Fruit Membranescontrasting
confidence: 76%
“…The combined analysis of all of these variables using a PCA clearly separated the vesicles into two groups depending on whether they came from juice or pulp. The PCA showed a positive correlation between a higher content of oleic acid (C18:1) and a higher antioxidant activity, which was also observed in hazelnuts 77 . Nevertheless, it was also observed that organic hazelnuts showed higher total sterol and sitosterol contents than conventional ones, whereas, in the present study, no significant differences were observed between the organic and conventional samples.…”
Section: Discussionsupporting
confidence: 63%
“…Farklı zamanlarda hasat edilen fındıkların biyometrik özellikleri Çizelge 1'de sunulmuştur. (Karaosmanoğlu, 2018). Bu nedenle fındıkların geç hasat edilmesi renk bozulmaları üzerinde pozitif etki sağlayabilir.…”
Section: Farklı Zamanlarda Hasat Edilen Fındıkların Meyve Ve Iç Boyut...unclassified
“…It contributes over 60% of the world's hazelnut production, followed by Italy (TEPGE, 2021). The consumption of hazelnut may provide potential health benefits (Brown et al, 2022) since it is a rich dietary source of protein, fiber, oleic acid, α‐tocopherol, β‐sitosterol, and vitamin E (Karaosmanoglu, 2022). Hazelnut products are used as a side ingredient by food and beverage manufacturers for making various products like chocolate, biscuits, pastries, ice cream, etc.…”
Section: Introductionmentioning
confidence: 99%